Does High‐Quality Auditing Mitigate or Encourage Private Information Collection?1. (28th August 2017) - Chen, Yangyang; Sadique, Shibley; Srinidhi, Bin; Veeraraghavan, Madhu
Abstract: The finance literature offers two competing possibilities on how investors respond to the quality of public financial statements in their pricing decisions. They could collect either (i) more private information to benefit from lower information collection cost, or (ii) less private information because of lower incremental benefits. In this paper, we use the audit setting to examine which possibility prevails. Using the idiosyncratic return volatility as a proxy for firm‐specific information, we show in a sample of 51, 559 firm‐year observations for 8, 261 U.S. firms spanning the period of 2000–2010 that firms audited by higher‐quality auditors exhibit lower average idiosyncratic return volatility but a higher concentration of it at the time of earnings announcements. Our findings are consistent with the argument that investors reduce private information collection in response to higher audit quality. Our findings are robust to alternative measures of audit quality and idiosyncratic return volatility.